A Systematic Review on the Occurrence of Antimicrobial-Resistant Escherichia coli in Poultry and Poultry Environments in Bangladesh between 2010 and 2021. (1st February 2023) - Islam, Md. Saiful; Hossain, Md. Jannat; Sobur, Md. Abdus; Punom, Sadia Afrin; Rahman, A. M. M. Taufiquer; Rahman, Md. Tanvir
Abstract : Antimicrobial resistance (AMR) is a significant public health issue in Bangladesh like many other developing countries where data on resistance trends are scarce. Moreover, the existence of multidrug-resistant (MDR) Escherichia coli exerts an ominous effect on the poultry sector. Therefore, the current systematic review, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, was conducted to find out the AMR scenarios in E. coli isolates sourced from poultry and poultry environments in Bangladesh between 2010 and 2021. Following the PRISMA guidelines, a total of 17 published scientific articles were selected for this systematic review. This review revealed that 18 out of 64 districts in Bangladesh reported E. coli in poultry, having a higher prevalence (combined prevalence: 69.3%, 95% confidence interval, CI: 67.3-71%). Moreover, the prevalence ranged from 24.3% to 100%. This review found that E. coli isolates showed resistance to 14 antimicrobial classes and 45 different antimicrobial agents, including the last-line (reserve group) antibiotics and banned antimicrobial categories for the treatment of infections in agricultural animals. Phenotypic resistance of E. coli against penicillins and beta-lactamase inhibitors (20.2%-100%), cephalosporins (1.9%-100%), fluoroquinolones (5.98%-100%), aminoglycosides (6%-100%), tetracyclines (17.7%-100%), carbapenems (13.6%-72.7%), macrolides (11.8%-100%), polymyxins (7.9%-100%), phenicols (20%-97.2%), sulfa drugs (44.7%-100%), cephamycins (21.4%-48.8%), nitrofurans (21.4%-63.2%), monobactams (1.2%), and glycylcyclines (2.3%) was recorded in the last decades in Bangladesh. Also, 14 articles reported MDR E. coli in poultry, including a 100% MDR in nine articles and a 92.7% (95% CI: 91.2-94%) combined percentage of MDR E. coli isolates. Twenty-four different AMR genes encoding resistance to beta-lactams ( bla TEM, bla CTX-M-1, bla CTX-M-2, bla CTX-M-9, bla OXA-1, bla OXA-47, bla SHV, and CITM ), colistin ( mcr1 and mcr3 ), fluoroquinolones ( qnrB and qnrS ), tetracyclines ( tetA, tetB, and tetC ), sulfonamides ( sulI and sulII ), trimethoprim ( dfrA1 ), aminoglycosides ( rmtB ), streptomycin ( aadA1 ), gentamicin ( aac-3-IV ), erythromycin ( ereA ), and chloramphenicol ( catA1 and cmlA ) were detected in E. coli isolates. The presence of MDR E. coli and their corresponding resistance genes in poultry and poultry environments is an alarming issue for all health communities in Bangladesh. We suggest a regular antimicrobial surveillance program with a strong One Health approach to lessen the hazardous effects of AMR E. coli in poultry industries in Bangladesh.